Relationship between mental health and academic performance among accounting students in Universiti Teknologi Malaysia - Tan Pei Sien, 1981-, author; Hishamuddin Mohd. Ali, supervisor; Fakulti Pengurusan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Psikologi Dengan Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2017